Silicon-based negative electrode material and preparation method and application thereof

By using the structure of silicon-based negative electrode material core, graphene oxide cladding and chemical crosslinking cladding in the silicon-based negative electrode material, the problem of volume expansion of silicon-based materials during charging and discharging is solved, and the performance improvement of the battery is achieved and increase in energy density.

CN119400837APending Publication Date: 2025-02-07福建龙净储能电池有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411583165.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The silicon-based negative electrode material has serious volume expansion problems during the charging and discharging process, resulting in poor rupture, powdering and circulation performance of the electrode material.

Method used

Using the negative electrode material structure consisting of a silicon-based material core, graphene oxide cladding and chemical crosslinking cladding, the graphene oxide cladding inhibits volume expansion, and the chemical crosslinking cladding provides a three-dimensional porous network structure to reserve. Expansion space and improve conductivity.

Benefits of technology

It effectively suppresses the volume expansion of silicon-based materials, improves the first-effect, cycle and rate performance of the battery, and improves the energy density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400837A_ABST
    Figure CN119400837A_ABST
Patent Text Reader

Abstract

The invention provides a silicon-based negative electrode material and a preparation method and application thereof. The silicon-based negative electrode material sequentially comprises a silicon-based material core, a graphene oxide coating layer and a chemical crosslinking coating layer from inside to outside, the chemical crosslinking coating layer comprises a crosslinking product of a conductive polymer material and a flexible polymer material. According to the silicon-based negative electrode material provided by the invention, the volume expansion of the silicon-based material can be inhibited, an expansion space is reserved, and the conductivity of the silicon-based negative electrode material is also improved, so that the first efficiency, the cycle performance and the rate capability of the silicon-based negative electrode material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries and relates to a silicon-based negative electrode material and a preparation method and application thereof. Background Art

[0002] With the rapid development of electric vehicles and energy storage, the low theoretical capacity (372mAh / g) of traditional graphite negative electrode materials can no longer meet people's needs. Silicon (Si) negative electrode materials have the advantages of high theoretical specific capacity (4200mAh / g), environmental friendliness, low voltage platform, and abundant resources. However, the serious volume expansion (>300%) of silicon during the charging and discharging process causes the electrode material to rupture or even pulverize, resulting in its extremely poor cycle performance. At the same time, its own poor conductivity will also restrict its development.

[0003] In view of the fact that silicon is easy to pulverize during the charging and discharging process, the current solutions include nano-sizing, porous (porous silicon carbon) and composite (such as silicon oxygen negative electrode material) of silicon materials. However, the above-mentioned improved methods still have problems to varying degrees; for example, CN103367727A adopts nano-silicon sandwiched between the gaps of granular graphite to coat nano-silicon / graphite polymer with organic cracked carbon. Although it avoids the side reactions caused by the contact between nano-silicon and electrolyte and leaves space for the expansion of nano-silicon, it improves the material's cycle performance to a certain extent. However, there is agglomeration of nano-silicon during the preparation process, and the expansion of nano-silicon itself during the cycle. The long cycle process still has the fragmentation of granular organic cracked carbon, which causes the nano-silicon to directly contact the electrolyte, resulting in a decrease in the cycle. Another example is CN116344778A, which discloses a low-expansion silicon-carbon negative electrode material and a preparation method thereof, which mainly relates to the field of lithium-ion batteries. The invention comprises silicon-carbon particles, wherein the silicon-carbon particles comprise composite particles of porous material and nano-scale silicon-based material, a carbon coating layer, graphite and organic cracked carbon; the structure of the composite particles of porous material and nano-scale silicon-based material is a silicon layer of nano-scale silicon-based material deposited in the pores of the porous material. The silicon-carbon material in the document needs to have a certain limit on the silicon content. When the silicon content is too high, the expansion is still large, which will cause the electrode structure to be damaged.

[0004] Even if the silicon material is composited to obtain silicon-oxygen negative electrode material or silicon-carbon negative electrode material, there will still be a large volume expansion problem. For example, the silicon-oxygen negative electrode material still has a large volume expansion (>200%) during the process of lithium insertion and extraction, resulting in the continuous formation of a thicker SEI film and a new solid interface, which leads to lower first efficiency and cycle performance. At the same time, its lower conductivity will also lead to lower rate performance.

[0005] Therefore, how to effectively inhibit the volume expansion of silicon-based negative electrode materials and improve their initial efficiency, cycle and rate performance is a technical problem that needs to be solved urgently. Summary of the invention

[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a silicon-based negative electrode material and a preparation method and application thereof. The silicon-based negative electrode material provided by the present invention can not only inhibit the volume expansion of the silicon-based material, but also reserve expansion space, and at the same time improve the conductivity of the silicon-based negative electrode material, thereby improving its first efficiency, cycle performance and rate performance.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a silicon-based negative electrode material, which includes, from the inside to the outside, a silicon-based material core, a graphene oxide coating layer, and a chemically cross-linked coating layer; the chemically cross-linked coating layer includes a cross-linked product of a conductive polymer material and a flexible polymer material.

[0009] The silicon-based negative electrode material provided by the present invention has an inner graphene oxide coating layer that suppresses excessive volume expansion of silicon oxide during charge and discharge, while an outer chemical cross-linking coating layer further suppresses its volume expansion; and the cross-linked product of the conductive polymer material and the flexible polymer material in the chemical cross-linking coating layer has a three-dimensional porous network structure, which reserves expansion space for the internal stress caused by the volume expansion and contraction of the silicon-based material core during charge and discharge, and also provides a loose channel for the transmission of lithium ions, and the addition of the flexible polymer material improves the mechanical properties of the negative electrode plate; at the same time, the graphene oxide and the conductive polymer material also improve the conductivity of the silicon-based material core; thereby improving the first efficiency, rate and cycle performance of the silicon-based negative electrode material battery.

[0010] In the present invention, the coating materials and the coating sequence of the silicon-based material core, the reduced graphene oxide coating layer and the chemically cross-linked coating layer cooperate with each other. If the coating sequence is adjusted, the conductive three-dimensional network and the double-layer coating of graphene oxide cannot be achieved; and in the chemically cross-linked coating layer, the cross-linked product of the conductive polymer material and the flexible polymer material also further cooperates. Neither a pure conductive polymer material nor a pure flexible polymer material can obtain a conductive polymer three-dimensional network self-supporting structure.

[0011] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0012] Preferably, the silicon-based material core comprises at least one silicon-based particle.

[0013] In the present invention, the graphene oxide coating layer may coat one silicon-based particle or may coat a plurality of silicon-based particles.

[0014] Preferably, the D50 of the silicon-based particles is 0.05 to 5 μm, for example, 0.05 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm or 5 μm.

[0015] In the present invention, the D50 of the silicon-based particles is adjusted to 0.05-5 μm, the particles are smaller, the volume expansion changes less, the transmission path of Li ions is shorter, and it is more beneficial to the electrical performance.

[0016] Preferably, the material in the silicon-based material core includes any one of pure silicon material, silicon-carbon material or silicon-oxygen material, or a combination of at least two of them, preferably silicon-oxygen material.

[0017] In the present invention, there is no special limitation on the specific type of silicon-based materials, and the present invention is applicable to all silicon-based negative electrode materials with volume expansion problems; further, silicon-oxygen materials are selected as silicon-based particles to better improve the cycle performance.

[0018] In addition, the silicon-carbon material includes but is not limited to the material type of silicon material deposited inside porous carbon and the material type of a carbon coating layer coated on the surface of the silicon material.

[0019] The chemical formula of silicon oxide material is SiO x , wherein 1≤x≤2, for example 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 or 2, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0020] Preferably, the surface of the silicon-based material core is connected to the graphene oxide coating layer through an aminoamide condensation reaction.

[0021] In the present invention, the contact effect between the silicon-based material core and the graphene oxide coating layer is improved through the aminoamide condensation reaction, the close coating of the core and the graphene oxide coating layer is achieved, the transmission path of electrons and ions is shortened, and the electrical properties of the material are better improved.

[0022] For example, the aminoamide reaction can be achieved by modifying the surface of the silicon-based material with amino groups, modifying the surface of the graphene oxide with carboxyl groups, and using a condensation agent 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide (EDC).

[0023] Preferably, the graphene in the graphene oxide coating layer comprises reduced graphene oxide.

[0024] In the present invention, reduced graphene oxide is used as a coating layer to further improve the conductivity, rate performance and cycle stability of the material.

[0025] Preferably, the conductive polymer material and the flexible polymer material are cross-linked and bonded via borate ester bonds.

[0026] In the present invention, the conductive polymer material and the flexible polymer material are cross-linked by dynamic borate bonds, so that the conductive polymer material and the flexible polymer material are cross-linked by chemical bonds, thereby obtaining a three-dimensional porous conductive network structure, which has the advantages of more stable structure and cyclic stability. The conductive polymer and the flexible polymer are bonded by dynamic borate bonds and can be combined again after breaking, thereby further improving the cyclic stability of the material.

[0027] Preferably, the conductive polymer material contains amino groups, and the conductive polymer material includes any one of polyaniline, polyphenylene diamine or polypyrrole, or a combination of at least two of them.

[0028] In the present invention, in addition to the conductive polymer materials provided above, derivatives thereof, such as polyaniline derivatives, etc., may also be included; in addition, in addition to the conductive polymer materials containing an amino matrix, other types of conductive polymer materials are also applicable to the present invention.

[0029] Preferably, the flexible polymer material contains hydroxyl groups, and the flexible polymer material includes any one of polyvinyl alcohol, polyethylene glycol or sodium alginate, or a combination of at least two of them.

[0030] In the present invention, in addition to the flexible polymer material containing hydroxyl groups, the flexible polymer materials of other groups, which can be cross-linked with the conductive polymer material, are also applicable to the present invention, such as polyacrylic acid.

[0031] In the present invention, the amino groups in the conductive polymer material and the hydroxyl groups in the flexible polymer material are cross-linked through specific dynamic borate bonds to realize a three-dimensional conductive network structure, which is beneficial to the rapid transmission of electrons and ions, and the introduction of the flexible polymer is beneficial to improving the mechanical properties of the negative electrode material; at the same time, during the charge and discharge process of the battery, the dynamic borate bonds in the silicon-based negative electrode material can also be repeatedly broken and recombined, which is more conducive to the performance of the battery.

[0032] In a second aspect, the present invention provides a method for preparing the silicon-based negative electrode material as described in the first aspect, the preparation method comprising the following steps:

[0033] mixing the silicon-based material and the graphene oxide solution at one time to obtain an intermediate material;

[0034] Secondarily mixing the intermediate material and the chemical cross-linked product to obtain the silicon-based negative electrode material;

[0035] Wherein, the chemical cross-linked material includes a cross-linked product of a conductive polymer material and a flexible polymer material.

[0036] The preparation method provided by the present invention realizes a double-layer coating process for the inner core of the silicon-based material, thereby obtaining a silicon-based negative electrode material with excellent first efficiency, rate and cycle performance.

[0037] Preferably, the mass ratio of the silicon-based material to the graphene oxide is 10:(0.4-0.6), for example 10:0.4, 10:0.5 or 10:0.6, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0038] In the present invention, the mass ratio of the silicon-based material to the graphene oxide is adjusted to 10:(0.4-0.6), which further improves the integrity and uniformity of the graphene oxide coating layer.

[0039] Preferably, the surface of the silicon-based material is modified with amino groups.

[0040] Preferably, the surface of the graphene oxide is modified with carboxyl groups.

[0041] Preferably, the mixed solution after the first mixing is subjected to a drying treatment, and the drying treatment method includes freeze drying.

[0042] Preferably, the freeze-dried product is subjected to reduction heat treatment to obtain an intermediate material.

[0043] Specifically, the temperature of the reduction heat treatment in the present invention is 800-1200°C, such as 800°C, 900°C, 1000°C, 1100°C or 1200°C, and the time of the reduction heat treatment is 2-5h, such as 2h, 3h, 4h or 5h.

[0044] It should be noted that the present invention does not specifically limit the one-time mixing method, and the present invention is applicable to any method that can achieve the coating of graphene oxide on the surface of silicon-based materials, such as stirring coating, etc.

[0045] The present invention also does not specifically limit the method of modifying the surface of the silicon-based material with amino groups or the method of modifying the surface of the graphene oxide with carboxyl groups. The present invention is applicable to any conventional technical scheme for group modification.

[0046] Exemplarily, the present invention provides a method for modifying the surface of a silicon-based material with amino groups: a silane coupling agent modification method, that is, using a silane coupling agent to modify the silicon-based material.

[0047] Exemplarily, the present invention also provides a method for modifying the surface of graphene oxide with carboxyl groups:

[0048] 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide were added to the graphene oxide solution at a molar ratio of 1:1, and stirred at room temperature to activate the carboxyl groups.

[0049] Optionally, the mixed solution is subjected to solid-liquid separation (such as centrifugation), washed (such as water washing and alcohol washing), and then freeze-dried.

[0050] It can be understood that the intermediate material in the present invention is a product structure in which graphene oxide covers a silicon-based material core.

[0051] Preferably, the secondary mixing comprises: secondary mixing of the intermediate material, the monomer material of the conductive polymer material, the flexible polymer material solution, the initiator, the crosslinking agent and the solvent, and crosslinking and coating to obtain a gel-state substance.

[0052] In the present invention, a cross-linked product of the conductive polymer material and the flexible polymer material is obtained during the cross-linking and coating process and is coated on the surface of the intermediate material.

[0053] It can be understood that the monomer material of the conductive polymer material in the present invention matches the conductive polymer material, for example, it can be aniline monomer, phenylenediamine monomer, etc.

[0054] Preferably, the cross-linking agent comprises aminophenylborate hydrochloride.

[0055] It should be noted that when the cross-linking agent provided by the present invention is selected from the above substances, it is inevitable to add hydrochloric acid as a solvent for the cross-linking agent, and the concentration and amount of hydrochloric acid added can be adaptively selected and adjusted according to the specific amount of cross-linking agent added: for example, hydrochloric acid with a concentration of 6 mol / L can generally be selected.

[0056] Preferably, the gel-state material is subjected to secondary drying treatment to obtain the silicon-based negative electrode material.

[0057] Preferably, the secondary drying method comprises freeze drying.

[0058] Preferably, the mass fraction of the flexible polymer material solution is 9-12%, for example 9%, 9.5%, 10%, 10.5%, 11%, 11.5% or 12%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0059] Preferably, the mass ratio of the intermediate material to the monomer material of the conductive polymer material is (1-3):1, for example 1:1, 1.2:1, 1.5:1, 1.8:1, 2:1, 2.4:1, 2.5:1, 2.8:1 or 3:1, etc., preferably (1.2-2.4):1, but is not limited to the listed values, and other unlisted values ​​within this numerical range are also applicable.

[0060] In the present invention, by adjusting the mass ratio of the intermediate material to the monomer material of the conductive polymer material to (1-3):1, the content of the silicon-based material in the negative electrode active material is increased, and further adjusted to (1.2-2.4):1, the capacity of the silicon-based material is better utilized.

[0061] Preferably, the molar ratio of the cross-linking agent, the monomer material of the conductive polymer material and the flexible polymer material is (0.1-0.2):1.5:7.6, for example, 0.1:1.5:7.6, 0.11:1.5:7.6, 0.12:1.5:7.6, 0.13:1.5:7.6, 0.135:1.5:7.6, 0.14:1.5:7.6, 0.15:1.5:7.6, 0.16:1.5:7.6, 0.17:1.5:7.6, 0.18:1.5:7.6, 0.18:1.5:7.6 or 0.2:1.5:7.6, etc., preferably (0.11-0.135):1.5:7.6, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0062] Preferably, the temperature of the cross-linking coating is -20 to 0°C, for example, -20°C, -18°C, -15°C, -13°C, -10°C, -8°C, -5°C, -3°C, -1°C or 0°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0063] The cross-linking coating process provided by the present invention realizes the formation of a three-dimensional conductive network of a cross-linked product with good conductivity under the action of a cross-linking agent at low temperature, thereby improving the electron and ion transmission capacity of the negative electrode material. By further regulating the temperature to -20°C to 0°C, a cross-linked product with a more stable and complete structure and better conductivity can be obtained, and the reaction is more uniform and more efficient.

[0064] Preferably, the cross-linking coating time is 4 to 12 hours, for example 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours or 12 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0065] Preferably, during the secondary mixing process, the pH value is <1.

[0066] In a third aspect, the present invention provides a negative electrode plate, comprising a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector, wherein the negative electrode active material layer comprises the silicon-based negative electrode material as described in the first aspect or the negative electrode material prepared by the preparation method as described in the second aspect.

[0067] In a fourth aspect, the present invention provides a self-supporting negative electrode plate, wherein the self-supporting negative electrode plate is composed of the silicon-based negative electrode material as described in the first aspect.

[0068] The chemically cross-linked coating layer in the silicon-based negative electrode material provided by the present invention has a three-dimensional porous network structure, and a self-supporting negative electrode plate can be directly prepared. Without a current collector, a binder and a conductive agent, a negative electrode plate with good mechanical properties and cycle performance can be obtained, and the energy density of the battery is effectively improved; and the self-supporting negative electrode plate only contains silicon-based negative electrode material, that is, the silicon-based negative electrode material and the self-supporting negative electrode plate are only different in the molded form, and the materials therein are still the same.

[0069] In a fifth aspect, the present invention provides a method for preparing the self-supporting negative electrode sheet as described in the fourth aspect, the preparation method comprising the following steps:

[0070] first mixing a silicon-based material and a graphene oxide solution to obtain an intermediate material;

[0071] Second, the intermediate material and the chemical cross-linking material are mixed to obtain negative electrode slurry, and the negative electrode slurry is cross-linked to form the self-supporting negative electrode sheet.

[0072] Preferably, the chemical cross-linking material raw materials include monomer materials of conductive polymer materials, flexible polymer material solution, initiator, cross-linking agent and solvent.

[0073] Preferably, the mass fraction of the flexible polymer material solution is 9-12%.

[0074] Preferably, the mass ratio of the intermediate material to the monomer material of the conductive polymer material is (1-3):1, preferably (1.2-2.4):1.

[0075] Preferably, the molar ratio of the crosslinking agent, the monomer material of the conductive polymer material and the flexible polymer material is (0.1-0.2):1.5:7.6, preferably (0.11-0.135):1.5:7.6.

[0076] Preferably, the cross-linking molding method includes mold cross-linking molding.

[0077] In the present invention, except for the mold cross-linking molding method, the other preparation processes for preparing the formed negative electrode plates are also applicable to the present invention.

[0078] Preferably, the temperature of the cross-linking molding is -20 to 0°C, and the time of the cross-linking molding is 4 to 12 hours.

[0079] Preferably, during the second mixing and cross-linking molding process, the pH value is less than 1.

[0080] That is, the preparation method of the self-supporting negative electrode in the present invention and the preparation method of the silicon-based negative electrode material only differ in the preparation process during the molding process, and the rest of the preparation process is consistent with the preparation process of the silicon-based negative electrode material. The definition of maintaining consistency in the present invention is that, except for the obvious difference in the cross-linking molding process, the rest including the raw materials, preparation process and preparation parameters are exactly the same.

[0081] In a sixth aspect, the present invention further provides a lithium-ion battery, wherein the lithium-ion battery comprises the negative electrode sheet as described in the third aspect or the self-supporting negative electrode sheet as described in the fourth aspect.

[0082] Compared with the prior art, the present invention has the following beneficial effects:

[0083] (1) The silicon-based negative electrode material provided by the present invention has a coating layer material and a coating sequence that cooperates with each other. The inner graphene oxide coating layer suppresses the excessive volume expansion of silicon oxide during the charge and discharge process, and the outer chemical cross-linking coating layer further suppresses its volume expansion. The cross-linked product of the conductive polymer material and the flexible polymer material in the chemical cross-linking coating layer has a three-dimensional porous network structure, which reserves expansion space for the internal stress caused by the volume expansion and contraction of the silicon-based material core during the charge and discharge process, and also provides a loose channel for the transmission of lithium ions. The addition of the flexible polymer material improves the mechanical properties of the negative electrode plate. At the same time, the graphene oxide and the conductive polymer material also improve the conductivity of the silicon-based material core. Thus, the first efficiency, rate and cycle performance of the silicon-based negative electrode material battery are improved.

[0084] (2) The chemically cross-linked coating layer in the silicon-based negative electrode material provided by the present invention has a three-dimensional porous network structure, which can be directly used to prepare a self-supporting negative electrode sheet without the need for a current collector, a binder, or a conductive agent, and can obtain good mechanical properties and cycle performance, thereby effectively improving the energy density of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0085] Figure 1 This is a schematic diagram of the structure and decomposition structure of the silicon-based negative electrode material provided in Example 1. DETAILED DESCRIPTION

[0086] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only used to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0087] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0088] In the description of the embodiments of the present application, the technical terms "primary", "secondary", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0089] Example 1

[0090] This embodiment provides a silicon-based negative electrode material, such as Figure 1 As shown, the silicon-based negative electrode material includes, from the inside to the outside, a silicon dioxide SiO2 core, a reduced graphene oxide rGo coating layer, and a chemically cross-linked coating layer; the chemically cross-linked coating layer includes a cross-linked product of polyaniline PANI and polyvinyl alcohol;

[0091] The silicon dioxide core and the reduced graphene oxide coating layer are connected through an aminoamide condensation reaction; polyaniline and polyvinyl alcohol are cross-linked through borate ester bonds to obtain a cross-linked product.

[0092] The preparation method of the silicon-based negative electrode material is as follows:

[0093] (1) adding 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide in a molar ratio of 1:1 to 1000 mL of graphene oxide (0.5 mg / mL) dispersion (aqueous solution), stirring at room temperature for 30 min to activate the carboxyl groups, and obtaining a mixed solution of graphene oxide with surface modified carboxyl groups;

[0094] Then, 10 g of amino-modified silica with a D50 of 100 nm was added to the mixed solution, and stirring was continued at room temperature for 24 h; the mixture was centrifuged for solid-liquid separation, washed with water and methanol, and freeze-dried to obtain a 24-hour graphene oxide-coated silica (GO@SiO2) precursor; the GO@SiO2 precursor was placed in a sintering furnace, argon gas was introduced at high temperature, and the mixture was kept at 1050°C for 3 h, and naturally cooled to room temperature to obtain an intermediate material rGo@SiO2 powder with a reduced graphene oxide-coated silica core;

[0095] (2) Prepare a 9% PVA solution;

[0096] Prepare the substrate solution: dissolve 0.0364 g of aminophenyl boronate (ABA) in 1.67 mL of HCl (6 mol / L), add deionized water and aniline monomer (AN) and mix evenly, add rGo@SiO2 powder and mix evenly, finally add PVA solution, continue stirring and mixing to obtain solution A, and place in an ice water bath for use. In the substrate solution, the mass ratio of the intermediate material to the aniline monomer is 1.2:1, and the molar ratio of ABA, AN and PVA is 0.11:1.5:7.6;

[0097] Prepare initiator solution: Dissolve 6.9 g of ammonium persulfate (APS) solution in 15 mL of deionized water to prepare APS solution, and place in an ice water bath for later use;

[0098] Take the APS solution and add it dropwise into the base solution at 10°C, stir evenly to change the color of the solution, and react at -20°C for 8 hours to obtain a gel structure. The molar ratio of APS to AN is 1.05. The hydrogel is soaked and washed with deionized water and ethanol, and finally the hydrogel is rapidly cooled and freeze-dried to obtain the silicon-based negative electrode material.

[0099] Example 2

[0100] This embodiment provides a silicon-based negative electrode material, which includes, from the inside to the outside, a silicon dioxide core, a reduced graphene oxide coating layer, and a chemically cross-linked coating layer; the chemically cross-linked coating layer includes a cross-linked product of polyaniline and polyvinyl alcohol;

[0101] The silicon dioxide core and the reduced graphene oxide coating layer are connected through an aminoamide condensation reaction; polyaniline and polyvinyl alcohol are cross-linked through borate ester bonds to obtain a cross-linked product.

[0102] The preparation method of the silicon-based negative electrode material is as follows:

[0103] (1) adding 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide in a molar ratio of 1:1 to 1000 mL of graphene oxide (0.5 mg / mL) dispersion (aqueous solution), stirring at room temperature for 30 min to activate the carboxyl groups, and obtaining a mixed solution of graphene oxide with surface modified carboxyl groups;

[0104] Then, 10 g of amino-modified silica with a D50 of 300 nm was added to the mixed solution, and stirring was continued at room temperature for 24 h; the mixture was centrifuged for solid-liquid separation, washed with water and methanol, and freeze-dried to obtain a 24-hour graphene oxide-coated silica (GO@SiO2) precursor; the GO@SiO2 precursor was placed in a sintering furnace, argon gas was introduced at high temperature, and the mixture was kept at 1050°C for 3 h, and naturally cooled to room temperature to obtain an intermediate material rGo@SiO2 powder with a reduced graphene oxide-coated silica core;

[0105] (2) Prepare a 9% PVA solution;

[0106] Prepare the base solution: dissolve 0.0416 g of aminophenyl boronate (ABA) in 1.67 mL of HCl (6 mol / L), add deionized water and aniline monomer (AN) and mix evenly, add rGo@SiO2 powder and mix evenly, finally add PVA solution, continue to stir and mix evenly to obtain solution A, and place in an ice water bath for use. In the base solution, the mass ratio of the intermediate material to the aniline monomer is 2.4:1, and the molar ratio of ABA, AN and PVA is 0.135:1.5:7.6;

[0107] Prepare initiator solution: Dissolve 6.9 g of ammonium persulfate (APS) solution in 15 mL of deionized water to prepare APS solution, and place in an ice water bath for later use;

[0108] Take the APS solution and add it dropwise into the base solution at 10°C, stir evenly to change the color of the solution, and react at -10°C for 10 hours (cross-linking and coating) to obtain a gel structure. The molar ratio of APS to AN is 1.05. The hydrogel is soaked and washed with deionized water and ethanol, and finally the hydrogel is rapidly cooled and freeze-dried to obtain the silicon-based negative electrode material.

[0109] Example 3

[0110] This embodiment provides a silicon-based negative electrode material, which includes, from the inside to the outside, a silicon dioxide core, a reduced graphene oxide coating layer, and a chemically cross-linked coating layer; the chemically cross-linked coating layer includes a cross-linked product of polyaniline and polyvinyl alcohol;

[0111] The silicon dioxide core and the reduced graphene oxide coating layer are connected through an aminoamide condensation reaction; polyaniline and polyvinyl alcohol are cross-linked through borate ester bonds to obtain a cross-linked product.

[0112] The preparation method of the silicon-based negative electrode material is as follows:

[0113] (1) adding 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide in a molar ratio of 1:1 to 1000 mL of graphene oxide (0.5 mg / mL) dispersion (aqueous solution), stirring at room temperature for 30 min to activate the carboxyl groups, and obtaining a mixed solution of graphene oxide with surface modified carboxyl groups;

[0114] Then, 10 g of amino-modified silica with a D50 of 100 nm was added to the mixed solution, and stirring was continued at room temperature for 24 h; the mixture was centrifuged for solid-liquid separation, washed with water and methanol, and freeze-dried to obtain a 24-hour graphene oxide-coated silica (GO@SiO2) precursor; the GO@SiO2 precursor was placed in a sintering furnace, argon gas was introduced at high temperature, and the mixture was kept at 1050°C for 3 h, and naturally cooled to room temperature to obtain an intermediate material rGo@SiO2 powder with a reduced graphene oxide-coated silica core;

[0115] (2) Prepare a 12% PVA solution;

[0116] Prepare the base solution: dissolve 0.0364 g of aminophenyl boronate (ABA) in 1.67 mL of HCl (6 mol / L), add deionized water and aniline monomer (AN) and mix evenly, add rGo@SiO2 powder and mix evenly, and finally add PVA solution, continue to stir and mix evenly to obtain solution A, and place it in an ice water bath for use. In the base solution, the mass ratio of the intermediate material to the aniline monomer is 2:1, and the molar ratio of ABA, AN and PVA is 0.11:1.5:7.6;

[0117] Prepare initiator solution: Dissolve 6.9 g of ammonium persulfate (APS) solution in 15 mL of deionized water to prepare APS solution, and place in an ice water bath for later use;

[0118] Take the APS solution and add it dropwise into the base solution at 10°C, stir evenly to change the color of the solution, and react at 0°C for 8 hours to obtain a gel structure. The molar ratio of APS to AN is 1.05. The hydrogel is soaked and washed with deionized water and ethanol. Finally, the hydrogel is quenched and freeze-dried to obtain the silicon-based negative electrode material.

[0119] Example 4

[0120] The difference between this embodiment and embodiment 1 is that the material in the core of this embodiment is an amino-modified nano-silicon material, the intermediate is rGO@Si, the cross-linked product is a cross-linked product of polyaniline and polyvinyl alcohol, and the negative electrode material is a cross-linked product and reduced graphene oxide double-coated nano-silicon;

[0121] In the preparation method, the amino silicon dioxide is replaced by amino nano silicon.

[0122] The rest of the preparation methods and parameters were the same as those in Example 1.

[0123] Example 5

[0124] The difference between this embodiment and embodiment 1 is that the conductive polymer material in this embodiment is polypyrrole, and the flexible polymer material is polyacrylic acid;

[0125] In the preparation method, the monomer is pyrrole.

[0126] The rest of the preparation methods and parameters were the same as those in Example 1.

[0127] Example 6

[0128] The difference between this embodiment and embodiment 1 is that the polyaniline and polyvinyl alcohol in this embodiment are physically cross-linked and entangled, that is, they are not cross-linked and bonded by borate bonds;

[0129] In the preparation method, no aminophenyl boronate hydrochloride crosslinking agent is added.

[0130] The rest of the preparation methods and parameters were the same as those in Example 1.

[0131] Example 7

[0132] The difference between this embodiment and embodiment 1 is that in step (2) of this embodiment, the mass ratio of the intermediate material to the aniline monomer is 1:1.

[0133] The rest of the preparation methods and parameters were the same as those in Example 1.

[0134] Example 8

[0135] The difference between this embodiment and embodiment 1 is that in step (2) of this embodiment, the mass ratio of the intermediate material to the aniline monomer is 3:1.

[0136] Example 9

[0137] The difference between this embodiment and embodiment 1 is that in step (2) of this embodiment, the temperature of cross-linking coating is 10°C.

[0138] The rest of the preparation methods and parameters were the same as those in Example 1.

[0139] Example 10

[0140] The difference between this embodiment and embodiment 1 is that the temperature of cross-linking coating in step (2) of this embodiment is -25°C.

[0141] The rest of the preparation methods and parameters were the same as those in Example 1.

[0142] Comparative Example 1

[0143] The difference between this comparative example and Example 1 is that in the silicon-based negative electrode material provided in this comparative example, the silicon-based negative electrode material includes a silicon dioxide core and a reduced graphene oxide coating layer from the inside to the outside, but does not include a chemically cross-linked coating layer.

[0144] In the preparation method, step (2) is not performed.

[0145] The rest of the preparation methods and parameters were the same as those in Example 1.

[0146] Comparative Example 2

[0147] The difference between this comparative example and Example 1 is that the silicon-based negative electrode material provided in this comparative example includes a silicon dioxide core and a chemically cross-linked coating layer from the inside to the outside, but does not include a reduced graphene oxide coating layer.

[0148] In the preparation method, the intermediate material in step (2) is directly replaced by a silicon dioxide material with a D50 of 100 nm.

[0149] The rest of the preparation methods and parameters were the same as those in Example 1.

[0150] Comparative Example 3

[0151] This comparative example provides a silicon-based negative electrode material, which includes a silicon dioxide SiO2 core, a polyaniline PANI coating layer and a reduced graphene oxide rGo coating layer from the inside to the outside;

[0152] The preparation method of the silicon-based negative electrode material is as follows:

[0153] Base solution preparation: 0.482 g SiO2 powder was dispersed in a mixture of 1.67 mL HCl (6 M), 450 μL deionized water and 276 μL A L, and placed in an ice water bath for later use;

[0154] 1.6 mL of APS solution was added dropwise to the substrate solution at 10 °C and reacted for 8 h to obtain a PANI@SiOx suspension, i.e., a polyaniline coating layer was coated on the surface of the silica core;

[0155] 0.024 g of reduced graphene oxide rGo was added to the PANI@SiOx suspension, stirred and mixed for 8 h, filtered and washed to neutrality, and vacuum dried to obtain a PANI@SiOx / rGo composite material.

[0156] Comparative Example 4

[0157] The difference between this comparative example and Example 1 is that in the silicon-based negative electrode material of this comparative example, the chemical cross-linked coating layer is replaced by a polyaniline coating layer;

[0158] In the preparation method, aminophenyl boric acid hydrochloride (ABA) and PVA solution are not added in step (2), and the polymerization reaction of aniline monomer is directly carried out.

[0159] The rest of the preparation methods and parameters were the same as those in Example 1.

[0160] The silicon-based negative electrode materials provided in Examples 1-10 and Comparative Examples 1-4 are used in negative electrode sheets, specifically as follows:

[0161] Application Example 1

[0162] This application example 1 provides a self-supporting negative electrode plate, wherein the self-supporting negative electrode plate is composed of the silicon-based negative electrode material provided in Example 1;

[0163] The method for preparing the self-supporting negative electrode sheet is as follows:

[0164] In step (2) of Example 1, the APS solution is added dropwise to the base solution at 10° C., stirred evenly to change the color of the solution, poured into a mold for molding, and reacted at -20° C. for 8 hours; the hydrogel is soaked and washed with deionized water and ethanol, and finally the hydrogel is rapidly cooled and freeze-dried to obtain the self-supporting negative electrode sheet;

[0165] The rest of the preparation process and parameters were the same as those in Example 1.

[0166] Application Example 2

[0167] This application example 2 provides a self-supporting negative electrode plate, wherein the self-supporting negative electrode plate is composed of the silicon-based negative electrode material provided in Example 1;

[0168] The method for preparing the self-supporting negative electrode sheet is as follows:

[0169] In step (2) of Example 2, the APS solution is added dropwise to the base solution at 10° C., stirred evenly to change the color of the solution, poured into a mold for molding, and reacted at -10° C. for 10 hours; the hydrogel is soaked and washed with deionized water and ethanol, and finally the hydrogel is rapidly cooled and freeze-dried to obtain the self-supporting negative electrode sheet;

[0170] The rest of the preparation process and parameters were the same as in Example 2.

[0171] Application Example 3

[0172] This application example 3 provides a self-supporting negative electrode sheet, wherein the self-supporting negative electrode sheet is composed of the silicon-based negative electrode material provided in Example 1; the preparation method of the self-supporting negative electrode sheet is as follows:

[0173] In step (2) of Example 3, the APS solution is added dropwise to the base solution at 10° C., stirred evenly to change the color of the solution, poured into a mold for molding, and reacted at 0° C. for 10 h; the hydrogel is soaked and washed with deionized water and ethanol, and finally the hydrogel is rapidly cooled and freeze-dried to obtain the self-supporting negative electrode sheet;

[0174] The rest of the preparation process and parameters were the same as those in Example 3.

[0175] Application Example 4

[0176] The difference between this application example and application example 1 is that this application example uses the silicon-based negative electrode material provided in embodiment 4 as the negative electrode material of the self-supporting negative electrode plate;

[0177] The intermediate is rGo@Si, the cross-linked product is the cross-linked product of polyaniline and polyvinyl alcohol, and the negative electrode material is polyaniline and reduced graphene oxide double-coated nano-silicon;

[0178] In the preparation method, the amino silicon dioxide is replaced by amino nano silicon.

[0179] The rest of the preparation methods and parameters are consistent with those in Application Example 1.

[0180] Application Example 5

[0181] The difference between this application example and application example 1 is that the conductive polymer material in this application example is polypyrrole, and the flexible polymer material is sodium alginate;

[0182] In the preparation method, the monomer is pyrrole.

[0183] The rest of the preparation methods and parameters are consistent with those in Application Example 1.

[0184] Application Example 6

[0185] This application example provides a negative electrode sheet of a non-self-supporting structure, the negative electrode sheet comprising a copper foil and a negative electrode active material layer located on one side of the copper foil; the negative electrode active material layer comprises the silicon-based negative electrode material in Example 6, a conductive agent (Super P) and a binder LA132. The silicon-based negative electrode material in Example 6 cannot obtain a self-supporting structure because the cross-linked product of polyaniline and polyvinyl alcohol is a pure physical cross-linking;

[0186] The preparation method of the negative electrode sheet is as follows:

[0187] The silicon-based negative electrode material in Example 6 was mixed with a conductive agent (Super P) and a binder LA132 (15wt%) in a mass ratio of 70:20:10 to prepare a slurry, which was coated on one side of a 10μm thick copper foil using a 150μm coater, dried in a vacuum oven, and rolled to obtain the negative electrode sheet.

[0188] Application Examples 7-10

[0189] The difference between Application Examples 7-10 and Application Example 1 is that the present application examples respectively use the silicon-based negative electrode materials provided in Examples 7-10 as the negative electrode materials of the self-supporting negative electrode sheets;

[0190] In the preparation method, the preparation parameters in Examples 7-10 are respectively regulated.

[0191] The rest of the preparation methods and parameters are consistent with those in Application Example 1.

[0192] Comparative Application Examples 1-4

[0193] The difference between comparative application examples 1-4 and application example 1 is that the present application examples respectively use the silicon-based negative electrode materials provided in comparative examples 1-4 as the negative electrode materials of the self-supporting negative electrode sheet;

[0194] In the preparation method, the regulation of the preparation process in Comparative Examples 1-4 respectively corresponds to the actual.

[0195] The rest of the preparation methods and parameters are consistent with those in Application Example 1.

[0196] The negative electrode sheets provided in Application Examples 1-10 and Comparative Application Examples 1-4 were used as negative electrodes, 1 mol / L LiPF6 electrolyte (volume ratio of ethylene carbonate and diethyl carbonate in the solvent = 1:1) was used, a polypropylene microporous membrane was used as a separator (Celgard2400 purchased from Celgard Company), and a lithium sheet was used as a counter electrode to assemble a button battery.

[0197] The electrochemical performance test of the battery was carried out on the Wuhan Blue Electric Battery Test System. The test conditions were:

[0198] (1) First efficiency performance: The assembled battery is charged at a constant current of 0.1C to a cut-off voltage of 2.5V, then charged at a constant voltage to a cut-off current of 0.01C, and then discharged at a constant current of 0.1C to a cut-off voltage of 0.01V. The discharge capacity is divided by the charge capacity to obtain the first charge and discharge efficiency, referred to as the first efficiency.

[0199] (2) Rate performance: The assembled battery was tested for first cycle charging capacity under 0.5C constant current charging conditions.

[0200] (3) Cycle performance: The assembled battery was tested on a battery testing system (Blue Electric Test System) and charged and discharged 200 times at a constant current of 0.1C in the voltage range of 0.01 to 2.5V under room temperature conditions. The retention rate after 200 cycles was obtained by dividing the 200th charge capacity by the first charge capacity.

[0201] The test results of the above tests are shown in Table 1.

[0202] Table 1

[0203]

[0204] From Table 1, we can get:

[0205] From the comparison of the data results of Application Example 4 and Application Example 1, it can be seen that the inner core becomes silicon nanoparticles, its capacity becomes larger, and the volume change during the charge and discharge process increases, but it still has good first efficiency, rate and cycle performance, and the effectiveness of the double-layer surface coating and the three-dimensional network structure.

[0206] From the comparison of the data results of Application Example 5 and Application Example 1, it can be seen that the conductive polymer and the flexible polymer are changed to PPy and sodium alginate, and their performance is slightly different from that of Application Example 1, indicating that this structure is also practical for other conductive polymers containing amino groups and flexible polymers containing hydroxyl groups.

[0207] From the comparison of the data results of Application Example 1 and Application Example 6, it can be seen that in the silicon-based negative electrode material provided by the present invention, if the crosslinking of the conductive polymer material and the flexible polymer material is purely physical crosslinking, and no chemical crosslinking bonding of the boron ester bond is performed, it is difficult to obtain a negative electrode sheet with a self-supporting structure, and only a conventional negative electrode sheet structure requiring a negative electrode current collector and a binder can be obtained, resulting in reduced performance capacity, first efficiency, rate and cycle performance.

[0208] From the comparison of the data results of Application Example 7 and Application Example 1, it can be seen that the proportion of the negative electrode active material rGO@SiOx is reduced relative to the conductive polymer, the active material is too little, the capacity is small, the conductivity is increased, and the rate and cycle are increased.

[0209] From the comparison of the data results of Application Example 8 and Application Example 1, it can be seen that if there is too much rGO@SiOx, the capacity should be increased, but more active materials lead to incomplete cross-linking of the conductive network, poor structural stability, reduced conductivity, poor capacity utilization, and slightly poor rate and cycle performance; from the comparison of the data results of Application Example 9 and Application Example 1, it can be seen that the cross-linking temperature is too high, and the PANI formed has poor conductivity, poor capacity utilization, and poor rate, cycle and other performances.

[0210] From the comparison of the data results of Application Example 10 and Application Example 1, it can be seen that the cross-linking temperature is too low, the energy consumption is large, and the reaction speed is too low, which is not conducive to actual production.

[0211] From the comparison of the data results of Application Comparative Example 1 and Application Example 1, it can be seen that there is no second layer of PANI conductive network coating, no self-supporting structure, poor conductivity, and a single layer coating cannot completely suppress the expansion of silicon oxide during the charge and discharge process. It needs to be mixed with inactive substances such as binders to form an electrode, and has poor capacity, rate and cycle performance.

[0212] From the comparison of the data results of Application Comparative Example 2 and Application Example 1, it can be seen that there is no rGO coating, but there is a PANI three-dimensional self-supporting conductive network, and the conductivity is relatively poor compared to rGO. The single-layer coating cannot completely inhibit the expansion of silicon oxide during the charge and discharge process, and has poor capacity, rate and cycle performance.

[0213] From the comparison of the data results of Application Comparative Example 3 and Application Example 1, it can be seen that the pure PANI conductive network coated silicon oxide, without the addition of cross-linking agent and flexible polymer, cannot form a three-dimensional network self-supporting structure, and needs to be mixed with inactive substances such as binders to form an electrode, and there is a simple physical mixture with rGO, without bond interaction. The single-layer rigid PANI molecular chain has a worse effect on inhibiting the expansion of silicon oxide during the charge and discharge process, and has poor capacity, rate and cycle performance.

[0214] From the comparison of the data results of Application Comparative Example 4 and Application Example 1, it can be seen that the rGO-coated silica structure, pure PANI molecular chain as the second coating layer, without the addition of cross-linking agent and flexible polymer chain, cannot form a three-dimensional network self-supporting structure, and the single-layer rigid PANI molecular chain coating has a smaller stress buffer for expansion and contraction relative to the PANI-PVA bonded molecules, and has poor capacity, rate and cycle performance.

[0215] In summary, the silicon-based negative electrode material provided by the present invention, the material of the coating layer and the coating order cooperate with each other, the inner graphene oxide coating layer suppresses the excessive volume expansion of silicon oxide during the charge and discharge process, and the outer chemical cross-linking coating layer further suppresses its volume expansion; and the cross-linked product of the conductive polymer material and the flexible polymer material in the chemical cross-linking coating layer has a three-dimensional porous network structure, which reserves expansion space for the internal stress caused by the volume expansion and contraction of the silicon-based material core during the charge and discharge process, and also provides a loose channel for the transmission of lithium ions, and the addition of the flexible polymer material improves the mechanical properties of the negative electrode plate; at the same time, the graphene oxide and the conductive polymer material also improve the conductivity of the silicon-based material core; thereby improving the first efficiency, rate and cycle performance of the silicon-based negative electrode material battery; and the silicon-based negative electrode material provided by the present invention can be directly prepared to obtain a self-supporting negative electrode plate, without the need for a current collector, a binder and a conductive agent, good mechanical properties and cycle performance can be obtained, and the energy density of the battery is effectively improved.

[0216] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A silicon-based negative electrode material, characterized in that: The silicon-based negative electrode material comprises, from the inside to the outside, a silicon-based material core, a graphene oxide coating layer and a chemically cross-linked coating layer; the chemically cross-linked coating layer comprises a cross-linked product of a conductive polymer material and a flexible polymer material.

2. The silicon-based negative electrode material according to claim 1, characterized in that: The silicon-based material core includes at least one silicon-based particle; Preferably, the D50 of the silicon-based particles is 0.05 to 5 μm; Preferably, the silicon-based material includes any one of pure silicon material, silicon-carbon material or silicon-oxygen material or a combination of at least two thereof, preferably silicon-oxygen material; Preferably, the surface of the silicon-based material core is connected to the graphene oxide coating layer through an aminoamide condensation reaction; Preferably, the graphene in the graphene oxide coating layer comprises reduced graphene oxide.

3. The silicon-based negative electrode material according to claim 1 or 2, characterized in that: The conductive polymer material and the flexible polymer material are cross-linked and bonded via borate ester bonds; Preferably, the conductive polymer material contains an amino group, and the conductive polymer material includes any one of polyaniline, polyphenylene diamine or polypyrrole, or a combination of at least two thereof; Preferably, the flexible polymer material contains hydroxyl groups, and the flexible polymer material includes any one of polyvinyl alcohol, polyethylene glycol or sodium alginate, or a combination of at least two of them.

4. A method for preparing a silicon-based negative electrode material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: mixing the silicon-based material and the graphene oxide solution at one time to obtain an intermediate material; Secondarily mixing the intermediate material and the chemical cross-linked product to obtain the silicon-based negative electrode material; Wherein, the chemical cross-linked material includes a cross-linked product of a conductive polymer material and a flexible polymer material.

5. The preparation method according to claim 4, characterized in that: The mass ratio of the silicon-based material to the graphene oxide is 10:(0.4-0.6); Preferably, the surface of the silicon-based material is modified with amino groups; Preferably, the surface of the graphene oxide is modified with carboxyl groups; Preferably, the mixed solution after the first mixing is subjected to a drying treatment, and the drying treatment method includes freeze drying; Preferably, the freeze-dried product is subjected to reduction heat treatment to obtain an intermediate material.

6. The preparation method according to claim 5, characterized in that: The secondary mixing includes: The intermediate material, the monomer material of the conductive polymer material, the flexible polymer material solution, the initiator, the cross-linking agent and the solvent are mixed for a second time, and cross-linked and coated to obtain a gel-state substance; Preferably, the cross-linking agent comprises aminophenylborate hydrochloride; Preferably, the gel-state material is subjected to secondary drying treatment to obtain the silicon-based negative electrode material; Preferably, the secondary drying method comprises freeze drying; Preferably, the mass fraction of the flexible polymer material solution is 9-12%; Preferably, the mass ratio of the intermediate material to the monomer material of the conductive polymer material is (1-3):1, preferably (1.2-2.4):1; Preferably, the molar ratio of the crosslinking agent, the monomer material of the conductive polymer material and the flexible polymer material is (0.1-0.2):1.5:7.6, preferably (0.11-0.135):1.5:7.6; Preferably, the temperature of the cross-linking coating is -20 to 0°C, and the time of the cross-linking coating is 4 to 12 hours; Preferably, during the secondary mixing process, the pH value is <1.

7. A negative electrode plate, characterized in that: The negative electrode plate includes a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector, and the negative electrode active material layer includes the silicon-based negative electrode material according to any one of claims 1 to 3 or the negative electrode material prepared by the preparation method according to any one of claims 4 to 6.

8. A self-supporting negative electrode sheet, characterized in that: The self-supporting negative electrode plate is composed of the silicon-based negative electrode material as described in any one of claims 1-3.

9. A method for preparing a self-supporting negative electrode sheet as claimed in claim 8, characterized in that: The preparation method comprises the following steps: first mixing a silicon-based material and a graphene oxide solution to obtain an intermediate material; secondly, mixing the intermediate material and the chemical cross-linking material raw material to obtain negative electrode slurry, cross-linking the negative electrode slurry to obtain the self-supporting negative electrode sheet; Preferably, the chemical cross-linking material raw materials include monomer materials of conductive polymer materials, flexible polymer material solution, initiator, cross-linking agent and solvent; Preferably, the mass fraction of the flexible polymer material solution is 9-12%; Preferably, the mass ratio of the intermediate material to the monomer material of the conductive polymer material is (1-3):1, preferably (1.2-2.4):1; Preferably, the molar ratio of the crosslinking agent, the monomer material of the conductive polymer material and the flexible polymer material is (0.1-0.2):1.5:7.6, preferably (0.11-0.135):1.5:7.6; Preferably, the cross-linking molding method includes mold cross-linking molding; Preferably, the cross-linking molding temperature is -20 to 0°C, and the cross-linking molding time is 4 to 12 hours; Preferably, during the second mixing and cross-linking molding process, the pH value is less than 1.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the negative electrode sheet as claimed in claim 7 or the self-supporting negative electrode sheet as claimed in claim 8.

Citation Information

Patent Citations

  • Lithium ion battery silicon-carbon anode material and preparation method thereof

    CN103367727A

  • Low-expansion silicon-carbon negative electrode material and preparation method thereof

    CN116344778A